Characteristic Study of a Valve-Matched Flow Single-Piston Miniature Water-Hydraulic Pump - Tong Xing; Ying Huang; Cun Gao; Jian Ruan (IEEE Access, 2024)
A miniature single-piston valve flow-matching water-hydraulic pump is described in this paper, which designs with a unique double-face cam mechanism to achieve the reciprocating motion of the piston and a new flow-matching valve to adapt to the requirements of the frequency of flow-matching, and the use of a brushless DC motor to regulate the speed and control the flow of the pump. In this paper, the mechanical structure and working principle of this new type of water-hydraulic pump are described, the mathematical model of the valve flow distribution process is established, the transfer functions of the suction and drain process are obtained, and the relationship between the structural parameters of the distribution valve and the transient output characteristics of this type of water-hydraulic pump is simulated, and the simulation results show that the quality of the valve spool is the key factor affecting the switching speed of the distribution valve. The transient pressure and transient flow rate of the pump are studied experimentally, which reveals the pulsation law of the output characteristics of this single-piston pump, and lays a theoretical foundation for the design of a double-piston pulsation-free hydraulic pump.